Exchange Rate, COVID-19, and Stock Returns in Africa: Insights from Time-Frequency Domain - Samuel Kwaku Agyei; Ahmed Bossman; Emmanuel Asafo−Adjei; Oliver Asiamah; Vincent Adela; Cornelius Adorm−Takyi (Discrete Dynamics in Nature and Society)
We examine the co-movement between exchange rate (EXR) returns and stock (STK) returns in Africa amid COVID-19 in a time and frequency domain. Therefore, we employ the bi- and partial wavelet and the wavelet multiple correlation techniques using daily data from 13 February 2013 to 6 May 2021. Our findings divulge that COVID-19’s effect does not increase the intensity of the relationship between EXR and STK returns in Africa but causes a significant difference in the lead-lag relationship between the two assets. We find a strong likelihood for a high market integration between African markets in the long run, regardless of market conditions. Under general market conditions, South African (Namibian) equities have the lead/lag potential in the short and long run (intermediate term). Namibian stocks are the first to respond to shocks before all other remaining variables in the intermediate term, while in the long term, the South African EXR market is the last variable to experience shocks. Owing to the recently intensified alliances between African markets, investors should be wary of the specific African equities they include in their portfolios in the periods ahead. Policymakers are required to have an in-depth understanding of the nature of the co-movement between the variables to ensure timely and operative policy responses are rolled out to minimise adverse fluctuations in stocks and the local currencies.